PERANCANGAN FASILITAS PENYIMPANAN PRODUK TEMPE PADA UKM TEMPE TITIK 2 - Rio Arsendo Sinaga; Ganda Sirait (LPPM Universitas Putera Batam, 2024)
The redesign of storage facilities for tempe products at UKM Tempe Titik 2 using the Computerized Relative Allocation of Facilities Technique (CRAFT) is explored in this study. Facing challenges of inadequate storage space and disorganized product management, this research employs CRAFT to optimize storage layout considering factors such as distance, storage capacity, and operational efficiency. Data gathered through observation, interviews, and documentation analysis are analyzed using CRAFT to design an optimal storage facility. Results indicate significant improvements in storage efficiency and effective reduction in handling costs with the implementation of CRAFT. This study contributes to enhancing efficient storage facility design practices in SMEs, particularly in tempe production contexts.